Final Processing Techniques for Adi Waste Using Landfill Control Methods in Mamuju District - Asrudin, Asrudin; Desi, Natsar; Indrayani, Poppy (ASTONJADRO, 2023)
The existing condition of the Adi-adi Waste TPA still tends to be operated in the Open Dumping manner even though the construction of the TPA is designed with the concept of controlled landfill management. Therefore one of the aims of this research is to know the technical processing of Adi- adi Waste TPA from the planning and implementation aspects, as well as to design a development concept to increase work effectiveness in the landfill block area with the help of technological devices. This study uses a qualitative method with a descriptive approach. Methods of data collection through interviews, observation, and study of documents. In this research, it is known that the technical processing model tends to be open dumping Ë†which only covers land 2-3 times in one fiscal year. The design of the development concept in the technical aspect of processing is the use of a Garbage Truck Vehicle Detection Sensor combined with direction guide lights in the Garbage Cell area that is being operated.